Controversies in the prevention of spontaneous preterm birth in asymptomatic women: an evidence summary and expert opinion. (11th November 2020) - Goodfellow, Laura; Care, Angharad; Alfirevic, Zarko
Abstract : Preterm birth prevention is multifaceted and produces many nuanced questions. This review addresses six important clinical questions about preterm birth prevention as voted for by members of the UK Preterm Clinical Network. The questions cover the following areas: preterm birth prevention in 'low‐risk' populations; screening for asymptomatic genital tract infection in women at high risk of preterm birth; cervical length screening with cerclage or vaginal pessary in situ; cervical shortening whilst using progesterone; use of vaginal progesterone in combination with cervical cerclage; and optimal advice about intercourse for women at high risk of preterm birth. Tweetable abstract: What stumps preterm birth experts? Evidence summary and expert opinion on the top six clinical controversies as voted by members of the UK Preterm Clinical Network. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16544 .